Human Brain Microvascular Endothelial Cells and Umbilical Vein Endothelial Cells Differentially Facilitate Leukocyte Recruitment and Utilize Chemokines for T Cell Migration - Shumei Man; Eroboghene E. Ubogu; Katherine A. Williams; Barbara Tucky; Melissa K. Callahan; Richard M. Ransohoff (Clinical and Developmental Immunology)
Endothelial cells that functionally express blood brain barrier (BBB) properties are useful surrogates for studying leukocyte-endothelial cell interactions at the BBB. In this study, we compared two different endothelial cellular models: transfected human brain microvascular endothelial cells (THBMECs) and human umbilical vein endothelial cells (HUVECs). With each grow under optimal conditions, confluent THBMEC cultures showed continuous occludin and ZO-1 immunoreactivity, while HUVEC cultures exhibited punctate ZO-1 expression at sites of cell-cell contact only. Confluent THBMEC cultures on 24-well collagen-coated transwell inserts had significantly higher transendothelial electrical resistance (TEER) and lower solute permeability than HUVECs. Confluent THBMECs were more restrictive for mononuclear cell migration than HUVECs. Only THBMECs utilized abluminal CCL5 to facilitate T-lymphocyte migration in vitro although both THBMECs and HUVECs employed CCL3 to facilitate T cell migration. These data establish baseline conditions for using THBMECs to develop in vitro BBB models for studying leukocyte-endothelial interactions during neuroinflammation.